Rapid Prototyping of a Customized Cooling System for a Novel Crank Rocker Engine - Altaf, Khurram; Baharom, Masri; Rashid A. Aziz, A; A. Qayyum, Junaid; Jahanzaib, Mirza (International Journal of Engineering and Technology, 2018)
A novel internal combustion engine termed as Crank Rocker Engine has been developed at Universiti Teknologi PETRONAS (UTP) Malaysia. In the existing design, the engine cylinder is cooled through forced convection which is not efficient and malfunctioning of cooling system could lead to engine overheating. The objective of the current study is to develop a concept of an integrated and customized cooling system for the Crank-Rocker engine and to develop through rapid prototyping (RP). The proposed cooling system comprises of an integrated cooling water jacket around the engine cylinder, which works on the principle of forced convection. The forced convection is energy intensive and not suitable for stationary engines. Therefore, an enhanced design of the cooling system is required to improve the overall performance of the engine. Since the engine cylinder is curved, the conventional manufacturing technologies could be difficult to apply for the development of cooling system. For swift, precise and economic development as well as performance analysis of the cooling system, RP technique could be promising. In the present study, a customized and modified cooling system has been designed and developed through fused deposition modelling (FDM), an efficient RP technology. Design for additive manufacturing (DFAM) is applied to mitigate development time and support structures of the cooling system. The design is proposed by keeping in view the cooling performance and manufacturability.Â